Long-term outcomes of common atrioventricular valve plasty in patients with functional single ventricle - Misumi, Yusuke (Oxford University Press, 2014)
OBJECTIVES: Common atrioventricular valve (CAVV) regurgitation is widely known as a risk factor for mortality and Fontan completion in patients with functional single ventricle. Hence, we reviewed our surgical experience with CAVV plasty in Fontan candidates. METHODS: Staged Fontan strategy and extracardiac total cavopulmonary connection as Fontan modification were our principal approaches in 1995. Since then, 38 consecutive Fontan candidates (21 males, median weight at operation was 7.0 kg and median age was 17 months old) underwent CAVV plasty. Right atrial isomerism was associated with 24 patients. The initial CAVV plasty was performed before inter-stage bidirectional Glenn (BDG) in 3 patients, at BDG in 23, before Fontan in 4 and during Fontan in 8. Since 1995, the modified Alfieri technique with a tailed, expanded, polytetrafluoroethylene tube as a bridging strip was the procedure for repair and 27 patients underwent the procedure. The mean follow-up period was 7.1 years (range 0–17 years). RESULTS: Actuarial survival and freedom from CAVV replacement rates at 1, 5 and 10 years were 81, 70 and 67% and 89, 85 and 75%, respectively. Seven patients ultimately underwent CAVV replacement with one death. Twenty-three of the 38 patients completed Fontan operation (61%). Association with total anomalous pulmonary venous connection (P= 0.01) and CAVV plasty before BDG (P= 0.05) were risk factors for mortality. CONCLUSIONS: CAVV plasty for patients with functional single ventricle is still challenging; however, the aggressive and repeated surgical intervention may contribute to provide better life-prognosis. The ventricular volume unloading effect of BDG without additional pulmonary blood flow or Fontan operation did not contribute to maintain CAVV function. Therefore, there would not be any hesitation for CAVV replacement to control CAVVR in the setting of systemic ventricular failure. Although the statistically significant therapeutic superiority of the modified Alfieri technique was not shown so far, further follow-up may reveal the advantage of this easy and simple technique.